2015
DOI: 10.1097/jto.0000000000000357
|View full text |Cite
|
Sign up to set email alerts
|

GM2-Activator Protein: A New Biomarker for Lung Cancer

Abstract: Our study demonstrates that GM2AP might serve as potential diagnostic and prognostic biomarkers in patients with lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 33 publications
1
8
0
1
Order By: Relevance
“…GM2A protein was reported to be a potential biomarker for lung cancer in an article by Potprommanee et al. and they found >5‐fold increase in the expression of GM2A in both urine and serum samples . Our study also showed the increased expression of GM2A in the urine samples of HE breast cancer patients suggests that GM2A may be a cancer‐specific urinary secreted protein.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…GM2A protein was reported to be a potential biomarker for lung cancer in an article by Potprommanee et al. and they found >5‐fold increase in the expression of GM2A in both urine and serum samples . Our study also showed the increased expression of GM2A in the urine samples of HE breast cancer patients suggests that GM2A may be a cancer‐specific urinary secreted protein.…”
Section: Discussionsupporting
confidence: 76%
“…Potprommanee et al. have reported that human urinary GM2 activator protein is a potential biomarker for lung cancer . Morrissey et al.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic and proteomics-based biomarkers are two major types of biomarkers, which can be identified through tumor cells, urine, sputum, blood, or other body fluids [ 3 ]. Table 3 demonstrates numerous lung cancer markers [ 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 ].…”
Section: Biomarkers For Lung Cancer Detectionmentioning
confidence: 99%
“…In our study, the five-year overall survival rate is over 40% for NSCLC patients 22 23 24 25 , as most cases of patients who require surgery are diagnosed at a early clinical stage (I and II). However, we report a different follow-up period using survival curves as in Fig.…”
Section: Discussionmentioning
confidence: 67%